2021
DOI: 10.2217/bmm-2020-0856
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Soluble Receptor for Advanced Glycation End Products Isoforms and Advanced Glycation End Products in Long-Living Individuals

Abstract: Background: Circulating levels of soluble receptor for advanced glycation end products (sRAGE) and advanced glycation end products (AGEs) correlate with aging/cardiovascular risk, which is delayed in long-living individuals (LLIs). AGEs/sRAGE isoforms (cleaved RAGE [cRAGE] and secretory RAGE [esRAGE]) ratio is a valuable marker for disease risk. Results: We evaluated circulating sRAGE isoforms, and AGEs in LLIs (n = 95; 90–105 years) and controls (n = 94; 11–89 years). cRAGE decreased with age in controls and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…We previously showed that circulating levels of cRAGE, and not esRAGE, decline with aging in healthy subjects and LLIs [ 31 , 32 ]. Table 3 shows the Spearman correlations of AGEs, the different isoforms of sRAGE and their ratios with age in CTR and type 2 diabetes groups.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously showed that circulating levels of cRAGE, and not esRAGE, decline with aging in healthy subjects and LLIs [ 31 , 32 ]. Table 3 shows the Spearman correlations of AGEs, the different isoforms of sRAGE and their ratios with age in CTR and type 2 diabetes groups.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, total human sRAGE included the detection of both cRAGE and esRAGE variants (DY1145, Human RAGE DuoSet ELISA, R&D Systems Inc., MN, USA) and esRAGE concentration was evaluated by an ELISA assay with an antibody raised against the exclusive C-terminal amino acids (332–347) sequence (K1009-1, B-bridge International, CA, USA). cRAGE was determined by subtracting esRAGE from sRAGE as already described [ 29 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations